Exploring determinants of meeting planners' commitment to the business relationships with destination management companies. Issue 2 (3rd April 2017) - Shin, Jungyoung Tiffany; Jeong, Miyoung; Oh, Haemoon; Tierney, Erin
ABSTRACT: Although there is a demand for research on a business-to-business relationship between meeting planners and destination management companies, the current hospitality and tourism literature is insufficient in its attempt to understand the dynamics of this unique relationship. Recently, in the meeting industry, destination management companies have been recognized to experience a more challenging business environment due to the abundance of online vendor information which activates meeting planners' disintermediation of destination management company services. To provide more practical implications for these key meeting players, this study urges that the key factor that encourages meeting planners to continue using destination management companies is trust. Therefore, this study examines determinants of the trust–commitment relationship as a means for meeting planners to achieve a more sustainable relationship with destination management companies. Applying and extending social exchange theory, this study also explores the determinants of the future relationship (commitment or termination). Findings of this research will provide the industry with suggestions for their relationship development.